A Unifying Concept for Growth Trends of Trees and Forests – The “Potential Natural Forest” - Trouillier, Mario; van der Maaten-Theunissen, Marieke; Scharnweber, Tobias; Wilmking, Martin (Frontiers in Forests and Global Change, 2020)
Changes in the environment will alter the growth rate of trees and forests. Different disciplines assess such growth rates differently, for example with, tree-ring width data, forest inventories or with carbon-flux data from eddy covariance towers. Such data is used to quantify forests biomass increment, forest's carbon sequestration or to reconstruct environmental variables before instrumental records. However, raw measurement data is typically not considered to be representative for the average growth rate of trees or forests. Depending on the research question, the effects of certain environmental variables or effects of tree and forest structure have to be removed first. It can be challenging to define and quantify a growth trend that can answer a specific research question because trees and forests grow and respond to environmental change in multiple ways simultaneously, for example with altered radial increment, height growth and stand density. Further challenges pose time-lagged feedback loops, for example between height and radial increment or between stand density and radial increment. Generally, different environments will lead to different tree and forest structures, but because of tree’s longevity this change will take decades or even centuries. Consequently, there can be an offset between the present forest structure and what we term the potential natural forest (PNF): Similar to the potential natural vegetation (PNV), the potential natural forest represents that forest that would develop under the current environmental conditions in the absence of human intervention. Because growth rates are affected by the tree and forest structure, growth-trend estimates will differ between the present and the potential forest. Consequently, if the legacy effects of the past are not of interest, the potential natural forest is the theoretical baseline to correct and estimate growth trends.